Pengaruh Profitabilitas, Leverage, Dan Likuiditas Terhadap Nilai Perusahaan Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Periode 2019-2023 - Neng Anti Julyanti (CV. ITTC INDONESIA, 2025)
Study This aims To know the influence of profitability, leverage and liquidity to mark a company. Profitability is measured with return on assets (ROA), Leverage is measured with debt to assets (DAR), Liquidity is measured with current ratio, and company value is measured Tobin's Q. Population in study This is all manufacturing companies in the sub-sector food and beverage listed on the Indonesia Stock Exchange (BEI ) in the 2019-2023 period. Deep sample study This is 10 companies in a period time for 5 years. sub-sector food and beverage listed on the Indonesia Stock Exchange (BEI ) in the 2019-2023 period. Retrieval technique sample with use method purposive sampling. The research design used is quantitative.